Pengaruh Model Discovery Learning dalam Kemampuan Berpikir Kritis dan Cognitif Mahasiswa Program Studi Sistem Informasi - Wilda Susanti; Darmanta Sukrianto; Dochi Ramadhani (Universitas Negeri Padang, 2020)
This study aims to look at the effect of discovery learning models on students' critical and cognitive thinking abilities on the ability to solve programming problems. This study used a quasi-experimental method conducted on students of the Information Systems study program. The subjects used were morning class students as the experimental class and the evening class as the control class 2018/2019 with 60 students. Data collection techniques is essay test questions critical thinking skills. Data analysis is using t test. The results of the analysis show that tcounted > t table and the significant value is smaller than 0.05. Based on these results, it can be concluded that there is a significant influence on the Discovery Learning model on the critical thinking skills of Information Systems students added about the limitations, practical implications, social implications and the value of their originality